Comparison of right- and left-approach esophagectomy for esophageal cancer: a meta-analysis - Peng, Xiangdong; Luo, Jiwen; Ren, Jie; Liu, Wen; Xia, Banglin; Liu, Guixian (Frontiers in Oncology, 2026)
ObjectiveThis study aims to compare the effects of left and right thoracic approaches on patients undergoing esophagectomy.MethodsA search was conducted across PubMed, Embase, Cochrane, and Web of Science for randomized controlled trials, cohort studies, and non-randomized trials that evaluated the effects of the two approaches on patients with esophageal cancer up to March 19, 2025. Two reviewers independently screened the retrieved articles, extracted relevant data, and appraised the risk of bias. A meta-analysis was performed using Stata statistical software.ResultsA total of 21 studies were included. Compared with the left thoracic approach, the right approach had a longer surgical duration (mean difference [MD] = 77.51, 95% confidence interval [CI]: 53.19–101.84, P < 0.05), a higher number of lymph nodes removed (MD = 3.00, 95% CI: 0.30–5.69, P < 0.05), and a higher risk of anastomotic fistula (MD = 2.07, 95% CI: 1.49–2.88, P < 0.05), wound infection (MD = 1.68, 95% CI: 1.04–2.73, P < 0.05) and pulmonary complications (risk ratio = 1.39, 95% CI: 1.15–1.68, P < 0.01). There were no significant differences in the risk of chylothorax, postoperative hospital stays, long-term disease-free survival, or overall survival.ConclusionEsophagectomy through the right thoracic approach achieves more thorough lymph node dissection, but it is associated with an increased risk of longer surgical duration, anastomotic fistula, wound infection, and pulmonary complications.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251026319, identifier CRD420251026319.